Management skills to promote participation families in basic schools - Claudio Barrientos Piñeiro; Patricia Silva García; Serafín Antúnez Marcos (Pontificia Universidad Católica del Perú, 2016)
This article provides knowledge about the state of affairs on policies and dynamics surrounding the performance skills of school principals regarding the promotion of participation. Using a qualitative approach and methodology Case Study results showed traditionalist practices and promotion strategies, passive involvement of families, with minimum levels of participation were obtained. The management performance is presented restrictive weak presence of attitudes toward empathy, trust and do dialogic, thus weakening the commitment of parents to participate in schools. The importance it attaches to social skills, personal qualities and values that should mobilize managers to adequately promote parent and community participation is emphasized.